2016
DOI: 10.1103/physrevd.94.075013
|View full text |Cite
|
Sign up to set email alerts
|

Study of MSSM heavy Higgs bosons decaying into charginos and neutralinos

Abstract: A multitude of searches have already been performed by the ATLAS and CMS collaborations at the LHC to probe the heavy Higgses of the Minimal Supersymmetric Standard Model (MSSM) through their decay to the Standard Model particles. In this paper, we study the decay of the MSSM heavy Higgses into neutralino and chargino pairs and estimate the maximum possible branching ratios for these 'ino' modes being consistent with the present LHC data. After performing a random scan of the relevant electroweakino parameters… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 146 publications
1
28
0
Order By: Relevance
“…To this end, in this paper we propose new LHC search strategies to broadly cover scenarios where these weakly interacting supersymmetric particles are produced from the decays of the heavy Higgs bosons, and we analyze their reach at the high luminosity (HL)-LHC. (Previous studies for heavy Higgs bosons decaying to electroweak particles can be found in [6,[14][15][16][17][18][19][20][21][22][23][24][25][26][27], and in Refs. [13,[28][29][30][31][32] for Next-to-Minimal-Supersymmetric-Standard-Model studies.).…”
Section: Introductionmentioning
confidence: 99%
“…To this end, in this paper we propose new LHC search strategies to broadly cover scenarios where these weakly interacting supersymmetric particles are produced from the decays of the heavy Higgs bosons, and we analyze their reach at the high luminosity (HL)-LHC. (Previous studies for heavy Higgs bosons decaying to electroweak particles can be found in [6,[14][15][16][17][18][19][20][21][22][23][24][25][26][27], and in Refs. [13,[28][29][30][31][32] for Next-to-Minimal-Supersymmetric-Standard-Model studies.).…”
Section: Introductionmentioning
confidence: 99%
“…A complete list of the searches for additional Higgses considered by us is summarized in Table II and Table III where some channels are taken from Ref. [33]. References [34,35] showed that the LHC searches for the charged Higgs fail to constrain the model for m H AE > 500 GeV.…”
Section: B Theoretical and Experimental Constraintsmentioning
confidence: 99%
“…Our phenomenological analyses [44,45] using ATLAS Run I data relaxed some of the above assumptions and showed that the constraints could be significantly weaker. However, all the above and several other recent phenomenological studies [46][47][48][49][50][51] invoked an adhoc 1 However co-annihilation of strongly interacting sparticles with the LSP may produce the observed DM in the universe [26,27].…”
Section: Introductionmentioning
confidence: 91%